Provincial Chinese Actors in Africa: The Case of Sichuan in Uganda - Xuefei Shi (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2016)
China has a system, referred to as duikou zhiyuan (对口支援, "twinning assistance"), in which developed provinces assisted less developed ones. A similar twinning system can also be found in China's foreign aid programs. For example, since 2006, China has funded 25 agro-technology demonstration centers (ATDCs) in Africa, most of which have contracts with teams from different Chinese provinces. This brief by Xuefei Shi looks specifically at Sichuan Province's projects in Uganda to assess how the twinning system has allowed Sichuanese companies to expand those aid relationships into business ventures. Shi argues that Sichuan companies have a big head start, and are likely to be able to expand in the local market at an unprecedented scale, outpacing their rivals from other Chinese provinces.
Keywords: 330